Vaquita: beleaguered porpoise of the Gulf of California, México - Würsig, Bernd; Jefferson, Thomas A.; Silber, Gregory K.; Wells, Randall S. (THERYA, 2021)
The vaquita (Phocoena sinus), an endemic porpoise of the Gulf of California, México, was first described scientifically in 1958, from three skulls. It is considered a sister taxon of an ancestor of the Southern Hemisphere Burmeisterâ€™s porpoise (P. spinipinnis) and spectacled porpoise (P. dioptrica), a case of antitropical distribution and speciation. Vaquita in modern times seem to have existed largely in waters 10 to 30 m deep of the very northern Gulf of California, and may have already existed in relatively low numbers by the 1950s and 1960s. The external appearance of the vaquita was not described until the late 1970s, and not until the 1980s and 1990s did additional information about ecology and biology emerge. Those studies and more recent shipboard and aerial visual line transect surveys, as well as stationary and boat-towed acoustic arrays, mapped occurrence patterns and approximate numbers in greater detail than before. The first credible estimates of abundance appeared in the 1990s, with numbers in the mid-hundreds and declining. While several reasons for the decline were originally postulated, mortality due to entanglement in nets has been established as the only known cause of decline, especially due to bycatch in large-mesh gillnets set for the endangered croaker fish totoaba (Totoaba macdonaldi). This fish is prized in China for human consumption of its swim bladder, generally ground up for purported therapeutic purposes. An extensive, lucrative fishery for totoaba, now illegal for many decades, has existed since at least the 1920s, and has recently increased. Although there have been laudable attempts to stem or halt totoaba fishing, these have largely been unsuccessful, and as of this writing the vaquita is on the brink of extinction. However, rapid concentrated action against illegal fishing with gillnets may yet save the species, and hope (with attendant action) must be kept alive. This overview is followed by an appendix of a previously unpublished popular essay by K.S. Norris describing when, where, and how he first discovered the species, and subsequent early work relative to this newly-described porpoise.